Reaction chemistry in rechargeable Li–O2 batteries. (18th April 2017) - Lim, Hee-Dae; Lee, Byungju; Bae, Youngjoon; Park, Hyeokjun; Ko, Youngmin; Kim, Haegyeom; Kim, Jinsoo; Kang, Kisuk
Abstract : This progress report reviews the most recent discoveries regarding Li–O2 chemistry during each discharge and charge process. Abstract : The seemingly simple reaction of Li–O2 batteries involving lithium and oxygen makes this chemistry attractive for high-energy-density storage systems; however, achieving this reaction in practical rechargeable Li–O2 batteries has proven difficult. The reaction paths leading to the final Li2 O2 discharge products can be greatly affected by the operating conditions or environment, which often results in major side reactions. Recent research findings have begun to reveal how the reaction paths may be affected by the surrounding conditions and to uncover the factors contributing to the difficulty in achieving the reactions of lithium and oxygen. This progress report describes the current state of understanding of the electrode reaction mechanisms in Li–O2 batteries; the factors that affect reaction pathways; and the effect of cell components such as solvents, salts, additives, and catalysts on the discharge product and its decomposition during charging. This comprehensive review of the recent progress in understanding the reaction chemistry of the Li–O2 system will serve as guidelines for future research and aid in the development of reliable high-energy-density rechargeable Li–O2 batteries.